2018
DOI: 10.3390/w10101302
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Suspended Sediment Concentrations and Loads from a Relatively Undisturbed Agroforested Catchment in the Northwest of the Iberian Peninsula

Abstract: The suspended sediment dynamics in small catchments are difficult to estimate accurately because they result from the coupling of complex processes occurring at different scales. In this study, the dynamics of suspended sediment concentrations (SSC) and loads were assessed in an agroforested humid catchment in NW Spain, based on a long-term rainfall, discharge and suspended sediment dataset (12 hydrological years) from high-frequency monitoring. The results highlight the episodic nature of sediment transport i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This could be due to the time lapse between the rains and their respective effect on the concentration and water level (Göransson et al, 2013). Other studies have reported similar results showing that the SSC did not necessarily change with discharge values which is an indication that other factors besides rainfall such as natural and anthropogenic disturbances control the SSC in small catchments (Ouellet-Proulx et al, 2016;Rodríguez-Blanco et al, 2018). Stenfert Kroese et al (2020a), in a study in the same catchment, reported that the impulse response between the peaks of discharge and sediment concentration was in general longer compared to the rainfall peak.…”
Section: Spatial and Temporal Trends Of Suspended Sediment Concentrationsmentioning
confidence: 81%
“…This could be due to the time lapse between the rains and their respective effect on the concentration and water level (Göransson et al, 2013). Other studies have reported similar results showing that the SSC did not necessarily change with discharge values which is an indication that other factors besides rainfall such as natural and anthropogenic disturbances control the SSC in small catchments (Ouellet-Proulx et al, 2016;Rodríguez-Blanco et al, 2018). Stenfert Kroese et al (2020a), in a study in the same catchment, reported that the impulse response between the peaks of discharge and sediment concentration was in general longer compared to the rainfall peak.…”
Section: Spatial and Temporal Trends Of Suspended Sediment Concentrationsmentioning
confidence: 81%